2005
DOI: 10.2516/ogst:2005028
|View full text |Cite
|
Sign up to set email alerts
|

Post-Combustion Decarbonisation Processes

Abstract: Résumé -Capture post-combustion -Dans le cas de la capture post-combustion, le CO 2 est séparé des gaz effluents. Ce procédé convient à la génération d'électricité conventionnelle et aux systèmes de conversion d'énergie. Les principaux procédés de conversion d'énergie et leurs performances sont décrits dans cet article. La technologie utilisée aujourd'hui, qui consiste à séparer le CO 2 des effluents gazeux à l'aide de solvants, est présentée et les principaux procédés sont discutés. Plusieurs pistes de dévelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…According to Bailey and Feron [83], higher CO 2 content in gas stream resulted in a higher driving force for absorption. Zhang et al [67] found that the absorption rate of CO 2 in MDEA + PZ was enhanced at elevated CO 2 partial pressure while Godini and Mowla [66] observed similar increased absorption efficiency with increasing of pressure for MEA system.…”
Section: Physical Properties Of Solventmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Bailey and Feron [83], higher CO 2 content in gas stream resulted in a higher driving force for absorption. Zhang et al [67] found that the absorption rate of CO 2 in MDEA + PZ was enhanced at elevated CO 2 partial pressure while Godini and Mowla [66] observed similar increased absorption efficiency with increasing of pressure for MEA system.…”
Section: Physical Properties Of Solventmentioning
confidence: 97%
“…CASTOR2 also showed significantly lower energy requirement than MEA [104]. While various researches are intensively conducted to produce new solvents with low regeneration heat duty, it should be noted that the sensible heat needed to raise the solvent from absorber to desorber temperature and the heat of evaporation required to produce the stripping steam in the reboiler should also be taken into consideration on top of the heat necessary to desorb the CO 2 from the solution (heat of absorption) [83,105].…”
Section: Major Challenges and Future Prospectsmentioning
confidence: 98%
“…This process route is ideally suited for conventional power stations and energy conversion systems. CO 2 at low partial pressure is separated from the gas stream after the fuel has been completely burned [2]. The flue gas from a typical post-combustion process is composed of 10-15% CO 2 , 70-75% N 2 and lower concentrations of other components.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the commercially-available technique for CO 2 capture is based on amine scrubbers [4,5]. However, this technology is energy-intensive and imposes various economic and environmental penalties including those due to the degradation of the expensive amine-based solvents [6,7].…”
Section: Introductionmentioning
confidence: 99%